Sleep quality and associated factors among people with asthma at public hospitals in east gojjam zone, North West Ethiopia, 2022. - Menberu Gete; Mezinew Sintayehu Bitew; Tirusew Wondie; Bekalu Bewket; Haile Amiha; Henok Mulugeta; Wuhabie Tsega Sahilu; Balew Adane; Aster Tadesse; Baye Tsegaye Amlak; Dejen Tsegaye Alem; Tiliksew Liknaw Alemneh; et al. (PLoS ONE)
Introduction The magnitude of poor sleep quality among people with asthma is widespread and has detrimental consequences, including a higher chance of having poor work performance, an increase in the frequency of asthma attacks, an increase in the need for overnight hospitalization, and a worse health related quality of life. However, it has not been well studied, especially in low-income countries like Ethiopia. This study's objective was to assess the degree of sleep quality and related factors among people with asthma who had follow-up visits at public hospitals in the East Gojjam Zone. Methods An institutional-based cross-sectional study design was conducted among 406 people with asthma through consecutive sampling techniques at public hospitals in East Gojjam Zone from June 6 to July 1, 2022. Sleep quality was measured by the Pittsburgh Sleep Quality Index through a face-to-face interview, and the collected data were entered into Epi Data version 4.4.2 and exported to SPSS version 25 for analysis. Logistic regression was fitted to assess the association between dependent and independent variables. Variables with a P-value <0.05 in multivariable logistic regression were considered statistically significant for the dependent variable. Results Among participants, 64.5% had poor sleep quality. Having anxiety (AOR = 2.67), comorbidity (AOR = 3.11), poor sleep hygiene practices (AOR = 2.99), severe asthma (AOR = 2.31), very poorly controlled asthma (AOR = 4.00) and current alcohol use (AOR = 3.20) were associated with poor sleep quality. Conclusion The magnitude of poor sleep quality was high in this study. Severe asthma, having comorbidity, very poorly controlled asthma, poor sleep hygiene practices, having anxiety symptoms and current use of alcohol were variables associated with poor sleep quality. Reduction in alcohol consumption, improving sleep hygiene practices, and treating comorbidities would be effective measures for improving poor sleep quality. Individuals with severe asthma and uncontrolled asthma symptoms need special attention.